A produção de texto dissertativo/argumentativo: uma abordagem das competências do ENEM - Basio, Daniela de Lima (2022)
Considering the proposals required by the booklets of the National High School Examination (ENEM), this article aims to analyze the textual productions carried out by students from a state public school. The production of texts in particular essay/argumentative is the basis for students in the preparatory phase for the entrance exam, who will enter universities throughout Brazil, however, it is noticed that they have linguistic deficiencies when producing. The theoretical basis of this study is centered on Antunes (2010) and Koch (2007), who discuss the study of the text, and on Dell' Isola (2007) on textual genre, and also on the skills required in ENEM, observing whether these are present in students’s productions. To develop this research, the ENEM booklets and the 2018 grade essays from the year 2018 were used as a basis/material. The analysis took into account the use of formal writing, the understanding of the most varied areas of knowledge, argumentation and defense from the point of view. The analysis showed that most students need to have an in-depth study of the structure and formation of the essay/argumentative text. Thus, it is concluded that the productions carried out in the classroom need to be oriented according to the school guidelines and the knowledge acquired by the teachers in the classroom, successfully developing the ENEM booklets, and the cohesion and coherence studies, thereby making students more accurately develop their textual skills.